Sex-specific Profiles of Blood Metal Levels Associated with Metal-Iron Interactions - Byung-Kook Lee; Yangho Kim (Elsevier, 2014)
The mechanisms by which iron is absorbed are similar to those of divalent metals, particularly manganese, lead, and cadmium. These metals, however, show different toxicokinetics in relation to menarche or menopause, although their interaction with iron is the same. This review focuses on the kinetics of these three toxic metals (manganese, lead, and cadmium) in relation to menarche, pregnancy, and menopause. The iron-manganese interaction is the major factor determining sex-specific differences in blood manganese levels throughout the whole life cycle. The effects of estrogen overshadow the association between iron deficiency and increased blood lead concentrations, explaining why women, despite having lower ferritin concentrations, have lower blood lead concentrations than men. Iron deficiency is associated with elevated cadmium levels in premenopausal women, but not in postmenopausal women or men; these findings indicate that sex-specific differences in cadmium levels at older ages are not due to iron-cadmium interactions, and that further studies are required to identify the source of these differences. In summary, the potential causes of sex-specific differences in the blood levels of manganese, lead, and cadmium differ from each other, although all these three metals are associated with iron deficiency. Therefore, other factors such as estrogen effects, or absorption rate as well as iron deficiency, should be considered when addressing environmental exposure to toxic metals and sex-specific differences in the blood levels of these metals.